Impact on psychological disorder in Covid-19: perspective of Bangladesh - Md Nazrul, Islam; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2022)
Introduction: COVID-19 is a pandemic concern now from the perspective of Bangladesh. Here, COVID-19 propagation is rising at an alarming rate. The COVID-19 pandemic plays a significant role in many individuals' psychological health and formed recent barriers for those already mentally ill. Global news, journals, and articles inform about psychological problems and their impact on our social life. Objectives: To identify impact of psychological disorder issues of COVID-19 among people in Bangladesh. Method: This review paper has established a secondary data collection method, and information was collected from different journals, periodicals, books and newspapers, etc. Results: The mental health of residents and employees is collectively affected by social trying to distance measures, compulsory lockdowns, isolated times, and apprehension of becoming sick, as well as the cessation of constructive behaviour, lost wages, and lack of self-confidence. Conclusion: This reviewed paper indicates appropriate government support, vaccination empowerment, and social awareness controlled through epidemics to minimize stress and sustain positive mental health.